Bees of the Lasioglossum series (Hymenoptera: Halictidae) in South Korea, with an illustrated keys to species - Murao, Ryuki; Lee, Heung-Sik; Tadauchi, Osamu (Zootaxa, 2015)
The South Korean fauna of the bee genus Lasioglossum Curtis (Halictidae: Halictini) belonging to the Lasioglossum series (i.e., those with the second submarginal crossvein strong) are reviewed. A total of 12 species are recognized for the country. Lasioglossum circularum Fan & Ebmer is recorded for the first time from the Korean Peninsula and the following species are newly recorded from South Korea: L. denticolle (Morawitz), L. formosae (Strand), L. kansuense (Blüthgen), L. occidens (Smith), L. sutshanicum Pesenko, and L. upinense (Morawitz). Bionomical data as well as illustrated keys to females and males of South Korean species are provided. DNA sequences including a part of barcode region are given for L. kansuense and L. occidens.